Índice de caminabilidad en las centralidades urbanas de los distritos de Huánuco, Amarilis y Pillco Marca - Barzola Gómez, Renato Edu (2022)
This work explores the urban built environment of Huánuco where the infrastructure of road spaces is almost exclusively for cars, motorcycles and tricycles. Thus, the work proposes to measure the urban built environment of three urban centers (Huánuco, Amarilis and Pillco Marca). Through the analysis of the walkability index based on four variables: environmental quality, density, pedestrian comfort and entropy, with instruments such as observation, mapping and analysis of spatial databases. A walkability index is constructed which allows us to understand the conditions of the existing urban built environment. The results allow us to identify that the urban centrality of the district of Amarilis presents better conditions in the variable of Environmental Quality, Density and Pedestrian Comfort that guarantee a better understanding at a local scale, this allows us to propose local policies for the improvement of urban spaces and to recover walkability in the centralities.